Treatment of indolent cutaneous T‐cell lymphoma with hypofractionated radiation therapy in three cats. Issue 5 (8th July 2021) - Chadsey, Laura E.; Cook, Matthew R.; Green, Eric E.; Jennings, Ryan N.; Moore, Peter F.; Vernau, William; Kisseberth, William C.; Diaz, Sandra F.
Abstract : Background: Feline indolent cutaneous T‐cell lymphoma (ICL) is an uncommon neoplastic disease. There is currently no consensus on treatment recommendations for ICL. Objective: To report the clinical outcome of three cats with ICL treated with hypofractionated electron‐beam radiotherapy (RT). Animals: Three privately owned cats with ICL. Materials and methods: Medical records and client surveys were reviewed. A diagnosis of probable ICL was based on history, clinical presentation and histopathological findings, and confirmed using CD3 immunohistochemical analysis and PCR for antigen receptor gene rearrangement (PARR). All cats were treated with hypofractionated RT (four fractions of 8 Gy). Results: All cats presented with skin lesions characterised by erythema and alopecia that were refractory to previous treatment with systemic glucocorticoids. Before hypofractionated RT treatment, lesions were histologically described as having diffuse infiltration of the dermis with CD3+ T cells. Molecular clonality analysis revealed clonal T‐cell receptor gamma gene rearrangement. After RT, two cats showed histological improvement defined by decreased infiltration of lymphocytes, with cellular infiltrate present only in the deeper dermis; one cat had near complete histological resolution of lesions with only minimal residual lymphocytes. One cat was determined to have a complete clinical response while the other showed partial responses. No acute adverse effects of radiation were observed; chronic effects included leukotrichia, partial alopecia and mild fibrosis. All clients reported improvement in quality of life for their cats. Conclusions and clinical importance: Clinical and histological improvement in these cats suggests that hypofractionated RT can be a useful treatment modality for cats with ICL Abstract : Background – Feline indolent cutaneous T‐cell lymphoma (ICL) is an uncommon neoplastic disease. There is currently no consensus on treatment recommendations for ICL. Objective – To report the clinical outcome of three cats with ICL treated with hypofractionated electron‐beam radiotherapy (RT). Conclusions and clinical importance – Clinical and histological improvement in these cats suggests that hypofractionated RT can be a useful treatment modality for cats with ICL. Résumé: Contexte: Le lymphome à cellule T cutané indolent félin (ICL) est une néoplasie rare. Il n'y a pas de consensus sur les recommandations de traitement pour l'ICL. Objectif: Décrire l'évolution clinique de trois chats avec ICT traités avec radiothérapie (RT) hypo‐fractionnée par faisceaux. Sujets: Trois chats de propriétaires avec ICL. Matériels et méthodes: Les données médicales et les suivis de clients ont été revus. Un diagnostic de probable ICL basé sur les commémoratifs, la présentation clinique et les données histopathologiques et confirmé par analyse immunohistochimique et PCR pour PARR (antigen receptor gene rearrangement). Tous les chats ont été traités par RT hypo‐fractionnée (quatre fractions de 8 Gy). Résultats: Tous les chats présentaient des lésions cutanées caractérisées par de l'érythème et de l'alopécie, réfractaires aux traitements antérieurs avec des corticoïdes systémiques. Avant le traitement par RT hypofractionnée, les lésions étaient histologiquement décrites comme une infiltration dermique diffuse avec CD3+. Une analyse moléculaire de clonalité a révélé un réarrangement clonal du gène gamma du récepteur cellulaire T. Après RT, deux chats ont montré une amélioration histologique définie par une diminution de l'infiltration de lymphocytes avec un infiltrat cellulaire présent uniquement dans le derme le plus profond; un chat avait une résolution quasi complète des lésions avec seulement des lymphocytes résiduels minimes. Un chat avait une rémission clinique complète alors que les autres présentaient des réponses partielles. Aucun effet indésirable aigu des radiations n'a été observé; les effets chroniques incluaient une leucotrichie, une alopécie partielle et une fibrose modérée. Tous les clients ont rapporté une amélioration de la qualité de vie de leur chat. Conclusions et importance clinique: L'amélioration clinique et histologique de ces chats suggère que la RT hypofractionnée peut être utile dans les modalités de traitement des chats avec ICL. Resumen: Introducción: el linfoma de células T cutáneo indolente felino (ICL) es una enfermedad neoplásica poco común. Actualmente no existe consenso sobre las recomendaciones de tratamiento para ICL. Objetivo: describir el resultado clínico de tres gatos con ICL tratados con radioterapia de haz de electrones (RT) hipofraccionada. Animales: tres gatos de propietarios particulares con ICL. Materiales y métodos: se revisaron los historiales médicos y las encuestas a los clientes. El diagnóstico de ICL probable se basó en la historia, la presentación clínica y los hallazgos histopatológicos, y se confirmó mediante análisis inmunohistoquímico de CD3 y PCR para el reordenamiento del gen del receptor de antígeno (PARR). Todos los gatos fueron tratados con RT hipofraccionada (cuatro fracciones de 8 Gy). Resultados: Todos los gatos presentaron lesiones cutáneas caracterizadas por eritema y alopecia refractarias al tratamiento previo con glucocorticoides sistémicos. Antes del tratamiento con RT hipofraccionada, histológicamente se describía que las lesiones presentaban infiltración difusa de la dermis con linfocitos T CD3 +. El análisis de clonalidad molecular reveló un reordenamiento del gen gamma del receptor de células T clonal. Después de la RT, dos gatos mostraron una mejoría histológica definida por una menor infiltración de linfocitos, con infiltrado celular presente solo en la dermis más profunda; un gato tuvo una resolución histológica casi completa de las lesiones con solo un mínimo de linfocitos residuales. Se determinó que un gato tuvo una respuesta clínica completa mientras que el otro mostró respuesta parcial. No se observaron efectos adversos agudos de la radiación; los efectos crónicos incluyeron leucotriquia, alopecia parcial y fibrosis leve. Todos los clientes informaron una mejora en la calidad de vida de sus gatos. Conclusiones e importancia clínica: la mejora clínica e histológica en estos gatos sugiere que la RT hipofraccionada puede ser una modalidad de tratamiento útil para los gatos con ICL. Zusammenfassung: Hintergrund: Das feline indolente kutane T‐Zell Lymphom (ICL) ist eine seltene neoplastische Erkrankung. Es gibt zurzeit keinen Konsens in Bezug auf Behandlungsempfehlungen für ICL. Ziel: Ein Fallbericht über das klinische Ergebnis dreier Katzen mit ICL, die mit hypofraktionierter Elektronenstrahl‐Radiotherapie (RT) behandelt worden waren. Tiere: Drei Katzen mit ICL, die in Privatbesitz waren. Material und Methoden: Die Patientenkarteien und Fragebögen von KlientInnen wurden durchgesehen. Die Diagnose einer möglichen ICL basierte auf der Anamnese, der klinischen Präsentation und den Histopathologie Befunden, und wurde mittels CD3 immunhistochemischer Analyse und PCR für Antigen Rezeptor Gen Rearrangement (PARR) bestätigt. Alle Katzen wurden mit hypofraktionierter RT (vier Fraktionen von 8 Gy) behandelt. Ergebnisse: Alle Katzen wurden mit Hautveränderungen vorgestellt, die durch Erythem und Alopezie charakterisiert waren, die nach einer vorangegangenen Behandlung mit systemischen Glukokortikoiden wieder auftraten. Vor der Behandlung mit hypofraktionierter RT wurden die Veränderungen histologisch als diffuse Infiltration der Dermis mit CD3+ Zellen beschrieben. Die molekulare Klonalitätsanalyse zeigte ein klonales T‐Zell Rezeptor Gamma Gen Rearrangement. Nach der RT zeigten zwei Katzen histologisch eine Verbesserung, die durch eine Abnahme der Lymphozyteninfiltration definiert wurde, wobei das zelluläre Infiltrat nur in der tieferen Dermis auftrat; eine Katze zeigte histologisch ein fast vollständiges Verschwinden der Veränderungen mit nur mehr minimalen Rest Lymphozyten. Bei einer Katze wurde festgehalten, dass sie eine völlige klinische Heilung zeigte, während die anderen nur eine partielle Verbesserung zeigten. Es wurden keine akuten Nebenwirkungen auf die Bestrahlung beobachtet; chronische Auswirkungen bestanden in Form einer Leukotrichie, teilweisen Alopezie und einer milden Fibrose. Alle BesitzerInnen berichteten von einer verbesserten Lebensqualität ihrer Katzen. Schlussfolgerungen und klinische Bedeutung: Die klinische und histologische Verbesserung bei diesen Katzen weist darauf hin, dass die hypofraktionierte RT eine nützliche Behandlungsmodalität für Katzen mit ICL sein kann. 要約: 背景: 猫の低悪性度皮膚T細胞リンパ腫 (ICL) は、まれな腫瘍性疾患である。現在、ICLの推奨治療法に関するコンセンサスはない。 目的: 本研究の目的は、低分割電子ビーム放射線療法 (RT) で治療されたICLの3頭の猫の臨床転帰を報告することであった。 被験動物: ICLを使用した3頭のオーナー所有猫。 材料と方法: 医療記録および顧客調査をレビューした。可能性のあるICLの診断は、病歴、臨床症状、および組織病理学的所見に基づいており、CD3免疫組織化学的解析および抗原受容体遺伝子再構成 (PARR) のPCR法を使用して確認された。すべての猫は低分割RT(8 Gyの4分割) で治療された。 結果: すべての猫は、以前の全身性糖質コルチコイドによる治療に抵抗性を示し、紅斑および脱毛症を特徴とする皮膚病変を呈した。低分割放射線治療の前に、病変は、CD3 + T細胞による真皮のびまん性浸潤を有すると組織学的に説明された。分子クローン性解析により、クローンT細胞受容体ガンマ遺伝子の再配列が明らかになった。 RT後、2頭の猫はリンパ球浸潤の減少によって定義される組織学的改善を示し、細胞浸潤は真皮深層にのみ存在した。 1頭の猫は病変のほぼ完全な組織学的消散を示し、リンパ球の残存は最小限であった。 1頭の猫は完全な臨床反応を示したが、もう1頭は部分的な反応を示した。放射線による急性の有害事象は観察されなかった。慢性の有害事象には、白血球除去症、部分的脱毛症、および軽度の線維症が含まれた。すべてのクライアントは、猫の生活の質の向上を報告した。 結論と臨床的重要性: これらの猫の臨床的および組織学的改善は、低分画RTがICL罹患猫にとって有用な治療法になり得ることを示唆している。 摘要: 背景: 猫惰性皮肤T细胞淋巴瘤(ICL)是一种不常见的肿瘤性疾病。目前对ICL的治疗建议尚未达成共识。 目的: 报告3只ICL猫接受大分割电子束放疗(RT)治疗的临床结果。 动物: 3只ICL私家猫。 材料和方法: 审查病历和客户调查。可能的ICL诊断是基于病史、临床表现和组织病理学结果, 并使用CD3免疫组织化学分析和抗原受体基因重排(PARR)的PCR进行证实。所有猫均采用大分割放疗(4次8 Gy) 。 结果: 所有猫均表现为皮肤病变, 特征为红斑和脱毛, 既往全身性糖皮质激素治疗难以控制。在大分割放疗治疗前, 病变在组织学上被描述为CD3+T细胞真皮弥漫性浸润。分子克隆性分析发现克隆性T细胞受体γ基因重排。RT后, 2只猫显示组织学改善, 定义为淋巴细胞浸润减少, 细胞浸润仅存在于较深的真皮中; 一只猫的病变几乎完全组织学消退, 仅有极少量残留淋巴细胞。一只猫确定为临床完全缓解, 而另一只猫显示部分缓解。未观察到放疗的急性不良反应; 慢性效应包括白毛症、部分脱毛和轻度纤维化。所有客户均报告其猫的生活质量改善。 结论和临床重要性: 这些猫的临床和组织学改善表明, 大分割RT可成为ICL猫的有用治疗方式。 Resumo: Contexto: O linfoma cutâneo indolente de células T em felinos (LCI) é uma doença neoplásica incomum. Não há consenso atual sobre as recomendações de tratamento para o LCI. Objetivo: Relatar o desfecho de três casos de LCI em gatos tratados com radioterapia hipofracionada por feixe de elétrons (RT). Animais: Três gatos de propriedade privada apresentando LCI Materiais e métodos: Foram revisados os prontuários e os questionários preenchidos pelos clientes. O diagnóstico de um provável LCI foi baseado no histórico, apresentação clínica e achados histopatológicos, e confirmado utilizando análise imunohistoquímica de CD3 e PCR para rearranjo do gene receptor do antígeno ( antigen receptor gene rearrangement – PARR). Todos os gatos foram tratados com RT hipofracionada (quatro frações de 8 Gy). Resultados: Todos os gatos apresentaram lesões cutâneas caracterizadas por eritema e alopecia refratárias aos tratamentos anteriores com glicocorticoides sistêmicos. Antes do tratamento com RT hipofracionada, as lesões histopatológicas descritas foram presença de infiltração difusa de células T CD3+ na derme. A análise molecular de clonalidade demonstrou rearranjo do gene gama de receptores de células T. Após a RT, dois gatos demonstraram melhora histológica caracterizada pela redução da infiltração de linfócitos e presença de infiltrado celular apenas na derme profunda; um gato apresentou quase resolução histológica completa restando apenas quantidade mínima de linfócitos residuais. Um gato apresentou resposta clínica completa, enquanto os outros apenas parcial. Não foram observadas reações adversas agudas à radiação; os efeitos crônicos observados foram leucotriquia, alopecia parcial e fibrose. Todos os clientes relataram melhora na qualidade de vida dos seus animais. Conclusões e importância clínica: A melhora clínica e histopatológica nesses gatos sugere que a RT hipofracionada uma modalidade terapêutica válida para gatos com LCI.